2006
DOI: 10.1677/joe.1.06727
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin stimulates GnRH secretion through the c-Src-PLC γ1 pathway in GT1–7 hypothalamic cells

Abstract: Serotonin is a neurotransmitter that alters the hypothalamicpituitary-adrenal axis. To date, however, the molecular mechanisms underlying the role of serotonin in hormone secretion have remained largely unclear. In this study, we report that serotonin activates phospholipase C (PLC) g1 in an Src-dependent manner in hypothalamic GT1-7 cells, and that pretreatment with either 4-amino-5-(4-chlorophenyl)-7-(t-butyl) pyrazole [3, 4-d] pyrimidine, an Src-kinase inhibitor, or U73122, a PLC inhibitor, attenuates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…However, 5-HT stimulates the release of GnRH through phospholipase C in vitro (Kim et al, 2006), postnatal exposure to citalopram did not influence the basal levels of GnRH mRNA in the POA and Kiss1 mRNA in the AVPV in this study. These results suggest that the gene expression of reproductive neuropeptides mediated by the serotonergic pathway could be controlled independently of AR expression.…”
Section: Total Activitiescontrasting
confidence: 74%
“…However, 5-HT stimulates the release of GnRH through phospholipase C in vitro (Kim et al, 2006), postnatal exposure to citalopram did not influence the basal levels of GnRH mRNA in the POA and Kiss1 mRNA in the AVPV in this study. These results suggest that the gene expression of reproductive neuropeptides mediated by the serotonergic pathway could be controlled independently of AR expression.…”
Section: Total Activitiescontrasting
confidence: 74%
“…Serotonin (5-HT) may stimulate the hypothalamus to release GnRH through the phospholipase C pathway (43) and function as a mediator of hormone secretion (44,45). We found the levels of 5-hydroxytryptophan, the immediate precursor of the neurotransmitter 5-HT, significantly decreased in the urine of CPP subjects, whereas the levels of 5-hdroxyindoleacetic acid and 5-hydroxykynurenamine were increased.…”
Section: Urinary Metabolites From Triptorelin and Derivatives-trip-mentioning
confidence: 94%
“…Some researchers report that GnRH is inhibited by serotonin and Dopamine (Cunningham et al, 2009). However, Kim et al (2006) indicated that serotonin increase GnRH. Based on peer reviewed literature blockade or inhibiting SERT by Sertraline will increase levels of serotonin in the synaptic cleft (Valenti et al, 2012).…”
Section: Discussionmentioning
confidence: 99%